Psychometric Properties Of The Intrinsic Motivation Inventory (Imi) Among Indonesian Student Futsal Athletes - Syahrinda, Yusuf Akbar; Juriana, Juriana; Deasyanti, Deasyanti; Rangkuti, Anna Armeini (Psychosophia: Journal of Psychology, Religion, and Humanity, 2025)
This study aimed to adapt and validate the Intrinsic Motivation Inventory (IMI) for Indonesian futsal student-athletes within the framework of Self-Determination Theory. A cross-cultural psychometric adaptation process was conducted, including translation, synthesis, back-translation, expert judgment, and field testing. Data were collected from 61 student-athletes, and content validity was assessed using Aiken’s V, yielding a strong result (V = 0.85). The IMI demonstrated good internal consistency (Cronbach’s α = 0.869) and significant interdimensional correlations, such as between perceived competence and enjoyment-interest (r = 0.516, p < .001). The mean intrinsic motivation score (M = 75.84) indicated a moderately high level of motivation among participants. These findings confirm that the adapted IMI is a valid and reliable instrument for measuring intrinsic motivation among futsal athletes in Indonesia. Theoretically, the study supports Self-Determination Theory in a team-sport context, and practically, it provides a culturally relevant tool for coaches and sport psychologists to assess and enhance athlete motivation.